1994
DOI: 10.1002/star.19940460802
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of Amylopectin without Long Range Order

Abstract: Weak amylopectin gels have been formed directly following dissolution of waxy maize granules. Rheological characterisation of these gels has been carried out as a function of stress and frequency. The gels are visually clear and homogeneous, and environmental scanning electron microscopy shows no trace of the original granules remaining. It is postulated that the origin of the gel network lies in pairwise aggregation of outer chains of the amylopectin molecules, presumably via double helix formation. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…5). Our observations are consistent with the idea that the origin of structure in gels is based on double-helical order , Gidley 1989, Cameron et al 1994. In the current study, no simple relationship was observed between the total enthalpy of each retrograded AP and AM (Table III) and the G′ of gels prepared from the fractions (Table IV).…”
Section: Dynamic Oscillatory Rheometry Of Nongranular Starches and Stsupporting
confidence: 91%
See 1 more Smart Citation
“…5). Our observations are consistent with the idea that the origin of structure in gels is based on double-helical order , Gidley 1989, Cameron et al 1994. In the current study, no simple relationship was observed between the total enthalpy of each retrograded AP and AM (Table III) and the G′ of gels prepared from the fractions (Table IV).…”
Section: Dynamic Oscillatory Rheometry Of Nongranular Starches and Stsupporting
confidence: 91%
“…Because the β-limit dextrins of amylopectin failed to form gels at similar concentrations and failed to develop turbidity when held at 1°C for one month, Ring et al (1987) suggested that the small chains involved in the gel network were the exterior chains of the amylopectin molecules. Based on the turbidity and rheological behavior of aqueous waxy maize starch dispersions at starch concentrations between 3 and 10.5%, Cameron et al (1994) suggested that the formation of infrequent intermolecular double helices between exter-nal chains of molecules, without formation of crystallinity, also contributes to the network structure of amylopectin gels. Jane and Chen (1992) fractionated potato, normal maize, and highamylose maize starch and prepared 8% (w/w) starch gels by codispersing the fractions (amylose:amylopectin, 1:4, w/w) in 0.5M KOH and neutralizing the dispersions to effect gelation.…”
mentioning
confidence: 99%
“…Noncrystalline double helices may occur on retrogradation because the double helices are not completely free to move into crystalline register: the branched molecules in starch may be a constraint to crystalline ordering during retrogradation. Cameron et al (1994) have suggested that the double helices from the outer chains in the amylopectin molecules do not aggregate to develop crystallinity. For these reasons, it may not be reasonable to predict a precise crystallization mechanism by fitting the Avrami equation to starch retrogradation data obtained by DSC.…”
Section: Kinetics Of Du Wx Starch Retrogradationmentioning
confidence: 99%
“…Studies regarding the contribution of long chains of amylopectin to its functionality have focused on increased interactions among external chains of amylopectin (Cameron, Durrani, & Donald, 1994;Klucinec & Thompson, 2002;Klucinec & Thompson, 1999;Miles et al, 1985;Ring et al, 1987). Based on the theory of Thompson (1999, 2002), two types of junction zones can form during amylopectin retrogradation affecting their functionality: (i) intermolecular double helices from external chains termed as the Type 1 junction zone where external chains from two different molecules form double helices, and (ii) an intramolecular double helix could participate in a semicrystalline aggregate with double helices from a separate molecule, forming an intermolecular aggregate of double helices of external chains as the Type 2 junction zone.…”
Section: Introductionmentioning
confidence: 99%